PRINCIPLE OF BALANCING REGULATION OF MINERAL MINING BUSINESS LICENSES FOR SUSTAINABILITY OF ENVIRONMENT - HOIRUDDIN HASIBUAN (UNTAG Law Review, 2019)
The principle of balance in the regulation of mineral and coal mining business permits is very important because it relates to environmental sustainability and the provisions of the legislation. The principle of balance as the implementation of the principle of good faith, the principle of honest transactions and the principle of justice will provide maximum benefits to humanity, people's well-being and personal development of citizens, the preservation of the nation's noble cultural values ? ? and environmental sustainability that is sustainable. This is important to maintain the balance of state rights in the control and management of natural resources and as a bridge between legal norms of good business principles. Mineral and stone mining business activitiesember must be based on the principle of good environmental management and control. The problem in this paper is how the urgency of the principle of balance in the issuance of mineral and coal mining business licenses based on environmental sustainability. This research is a type of research article using juridical analysis methods. The results showed that the application of the principle of balance must be present to maintain the continuity of natural support with the human needs whose arrangements are included in the law.